Christianity and Rationalism:: Maximus the Confessor vs. Descartes - Papaoikonomou, Antonis (Dia-noesis: A Journal of Philosophy, 2024)
Maximus the Confessor and René Descartes were influential thinkers in their respective historical and philosophical contexts, but their philosophical orientations and concerns were distinct. Maximus was primarily a Christian theologian who integrated faith and reason within a theological framework, while Descartes was a key figure in the development of modern philosophy, emphasizing individual reason and scepticism as foundational elements of his philosophical system. This paper aims to present some aspects of their philosophy and try to find common ground in their thought.